1989
DOI: 10.1002/bdd.2510100310
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of seven 50 mg and 100 mg nitrofurantoin tablets

Abstract: Four 50 mg and three 100 mg marketed nitrofurantoin tablets were studied in 14 healthy male subjects. Urine was collected 1, 2, 3, 4, 6, 8, 12, and 23 h after each dose, and nitrofurantoin was assayed by HPLC. The in vitro dissolution of the tablets was determined using USP Apparatus 1 and 2, with 0.1 N hydrochloric acid and pH 7.2 buffer as the dissolution fluids. One of the 50 mg tablets was more rapidly and completely absorbed than the other six products. The incidence of side-effects for this product was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In vitro studies demonstrated that increasing the moisture content of CBZ tablets by exposure to high humidity resulted in a lowering of the dissolution profile (Wang et al, 1990). Human studies show a strong relation between in vitro dissolution and in vivo bioavailability of CBZ (Wang et al, 1990) and other drugs (Skelly, 1976;Meyer et al, 1989). Therefore, it is not unexpected that tablets contaminated by direct exposure to water would dissolve poorly in vivo, resulting in reduced bioavailability and, as a consequence, low CBZ serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that increasing the moisture content of CBZ tablets by exposure to high humidity resulted in a lowering of the dissolution profile (Wang et al, 1990). Human studies show a strong relation between in vitro dissolution and in vivo bioavailability of CBZ (Wang et al, 1990) and other drugs (Skelly, 1976;Meyer et al, 1989). Therefore, it is not unexpected that tablets contaminated by direct exposure to water would dissolve poorly in vivo, resulting in reduced bioavailability and, as a consequence, low CBZ serum levels.…”
Section: Discussionmentioning
confidence: 99%